The Effect of Profitability, Liquidity, Leverage, and Activity Ratios on Dividend Policy in Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesia Stock Exchange in the 2016-2020 Period - Susellawati; Dewi Permata Sari; Septa Diana Nabella; Andi Hidayatul Fadlilah (Jurnal Mantik, 2022)
This study aims to determine the relationship between Profitability, Liquidity, Leverage, and Activity Ratios on dividend policy in manufacturing companies in the food and beverage industry sector that have been listed on the Indonesian stock exchange in the 2016-2020 period. And to find out whether there are problems with dividends that affect manufacturing companies in the food and beverage industry sector that have been listed on the Indonesia Stock Exchange from 2016 to 2020. The methodology used is Multiple Linear Analysis, Coefficient of Determination, T-test, and F test. It is concluded that this research has a significant effect on Profitability, Liquidity, Leverage, and Activity Ratios on dividend policy. ROA (X1) 0.044 < 0.05, CR (X2) 0.843 > 0.05, DER (X3) 0.307 > 0.05, Total Asset Turnover (X4) 0.006 < 0.05 and a significant value of 0.023 < from 0, 05 and the calculated F value is 3.312 > F table 2.64.